La fabrique locale des statistiques scolaires - Sarah Fichtner (Revue d'anthropologie des connaissances)
Based on 12 months of ethnographic research in a primary school in rural Benin, this paper focuses on the “little arrangements” organised around the local fabrication of school statistics, arising from the interaction between demands at international level and strategies and room for manœuvre at local level. Based on two key variables central to international policies of Education for All, namely school enrolment and repetition rates, this study shows how the actors involved in the school arena represent, govern and “do the school” through the production of these numbers. The data demonstrates that school statistics reflect the results of micro political strategies to enhance budget allocation and school reputation, and mirror the bureaucratic (self) control of the actors involved, rather than being reliable instruments that can inform or measure macro policies of development.